A large-scale genetic screen identifies genes essential for motility in Agrobacterium fabrum - Calvopina-Chavez, Diana G.; Howarth, Robyn E.; Memmott, Audrey K.; Pech Gonzalez, Oscar H.; Hafen, Caleb B.; Jensen, Kyson T.; Benedict, Alex B.; Altman, Jessica D.; Burnside, Brittany S.; Childs, Justin S.; Dallon, Samuel W.; DeMarco, Alexa C.; et al. (PLOS ONE, 2023)
The genetic and molecular basis of flagellar motility has been investigated for several decades, with innovative research strategies propelling advances at a steady pace. Furthermore, as the phenomenon is examined in diverse bacteria, new taxon-specific regulatory and structural features are being elucidated. Motility is also a straightforward bacterial phenotype that can allow undergraduate researchers to explore the palette of molecular genetic tools available to microbiologists. This study, driven primarily by undergraduate researchers, evaluated hundreds of flagellar motility mutants in the Gram-negative plant-associated bacterium Agrobacterium fabrum. The nearly saturating screen implicates a total of 37 genes in flagellar biosynthesis, including genes of previously unknown function.